Facility and Technological Supports, and Information Transparancy to Improve the Success of a Contract Farming between Farmers Group and Company - Agung Sinaga; Siwi Gayatri; Agus Subhan Prasetyo (Universitas Muhammadiyah Malang, 2022)
Contract farming is carried out to encourage the improvement of economic and social condition of farmer community so it can increase their income and achieve more equitable and sustainable development. The process of contract farming is affected by various factors, internal factors or external factors. This sudy aims to (i) describe contract farming between PT Bloom Agro and Bangkit Merbabu farmer group, (ii) describe the challenges and benefits of contract farming, and (iii) analyze the factors that effect the success of contract farming between PT Bloom Agro and Bangkit Merbabu farmer group. The research was conducted in Desa Batur, Kecamatan Getasan using the cencus method with the total population of 35 organic vegetable farmers in Bangkit Merbabu farmer group. The analysis method in this research was descriptive analysis and multiple linear regresion. The data analysis showed that the F test result of variable education, farming experience, production input, technological support and information transparancy simultaneously have a significant effect on the success of contract farming betwen PT Bloom Agro with Bangkit Merbabu farmer group. The t test result showed production input, technological support and transparancy of information individually have a significant efect on the success of contract farming. Pattern of contract farming that was applied between PT Bloom Agro and Bangkit Merbabu farmer group is a general trading contract. Covid-19 pandemic, climatic condition and limitation of education were found to be the inhibiting factors that farmers faced in the implementation of contract farming. PT Bloom Agro can provide more intensive assistance and training about contract farming to increase farmer’s knowledge and skill for sustainability of contract farming.